Assessing Fear-Avoidance Belief Questionnaire and Quality of Life in Housewives with Knee Osteoarthritis : A Research Protocol - Dhanashri R Ghordadekar1 , Angela Kapoor2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction - Osteoarthritis (OA) is an inflammatory disorder of cartilage, degeneration of synovial fluid,osteophyte formation, thinning of joint space and sub-chondral sclerosis. The prevalence of osteoarthritis inIndia was found to be around 28.7%. Females are generally more affected than males with the ratio of 2:1.Of all the joints knee and hip joint are seen to be most commonly affected joint in OA. Prevalence of kneepain is common amongst housewives due to prolong standing and frequent bending. Strenuous physicalactivity, especially activities requiring kneeling, knee-bending, stair climbing, squatting, prolonged standingas well as knee injury and trauma have also been linked to a high prevalence of symptomatic knee OA. KneeOA causes pain of various degree depending upon the severity of disease which can cause fear in patients.The fear related to pain can results in decrease in quality of life.Purpose - Purpose of this study was to assess fear amongst housewives related to OA using fear-avoidancebelief questionnaire and the effects of fear on their daily life using WHOQOL-BREF.Methodology - 200 housewives will be selected according to exclusion and inclusion criteria. Their kneeradiography was done to look for level of OA. Then those ladies were interview to find their fear related todisease and its effects and how that affects their quality of life.Results - Results are awaited till the study is completed.Conclusion - Conclusion of this study depends upon the result of this study.